Computer-aided diagnosis of pulmonary nodules from chest X-rays using rotation forest - Htike@Muhammad Yusof, Zaw Zaw; Nyein Naing, Wai Yan; Khan, Sheroz (2014)
A chest X-ray examination is a painless, non-invasive, and cost effective medical examination performed at present day. A pulmonary nodule is a small round lesion or mass in the lungs which can be indicative of an infection or a neoplasm. Chest X-rays can be used to diagnose pulmonary nodules. This paper proposes a three-layered framework to perform automatic diagnosis of pulmonary nodules. The first layer performs pre-processing of X-ray images. The second layer extracts texture features from the gray-level co-occurrence matrix. Finally, the third layer classifies whether the X-ray contains any signs of nodules using an ensemble technique called rotation forest. Experiments have been carried out on a chest X-ray dataset from the Japanese Society of Radiological Technology. Satisfactory preliminary experimental results demonstrate the efficacy of our computer aided pulmonary nodule diagnosis system.